Understanding gendered rice varietal trait preferences: Case of stress tolerant rice in Odisha - Puskur, Ranjitha (International Rice Research Institute, 2017)
Presented by Ranjitha Puskur (IRRI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.)